TELE FORENSIC TECHNOLOGICAL APPLICATION IN CRIME INVESTIGATION - Chetti, S O; Kokare, R N; Daundkar, B B (Journal of Forensic Medicine and Toxicology, 2017)
Teleforensic is the use of technology to transmit crime scene images and data in real time to personnel at a remote location or any location. However, teleforensic technology can be useful in Forensic, crime scene management, policing and for Bomb Detection & Disposal Squad team. The use of video conferencing technology in crime investigation is discussed in this paper. The teleforensic technological solution through satellite and other solutions like Vidyo Desktop software from National information centre, Lync software and Skype can be used in teleforensic. The advantages and limitations by using above techniques are also discussed in present paper. Considering the security and cost it is also conclude that VidyoDesktop from NIC can be the best solution for teleforensic.